Do Integrated Systems of Stroke Care Improve Symptom to Surgery Times in Patients with Symptomatic Carotid Stenosis? A Single Centre Decision Tree Analysis. (December 2018) - Mofidi, Reza; Thomas, Matthew; Wong, Peng F.; Bergin, Adrian; Young, Gavin
Abstract : Objective: The objective of this study was to examine the impact of an integrated system of stroke care on symptom to surgery times, cost-effectiveness, and quality of life measures in patients with symptomatic carotid stenosis. Methods: Patients who underwent carotid endarterectomy (CEA) in a regional vascular centre between April 1, 2011, and March 31, 2016, were identified from the National Vascular Registry (NVR). Risk of stroke on medical therapy for each patient was calculated using the Oxford stroke risk calculator. Symptom to surgery times were compared among patients referred from a stroke service providing an integrated stroke care and the stroke service in an adjacent NHS trust which provides standard urgent referral pathway. A decision analytic Markov process model was constructed to determine the cost-effectiveness of CEA versus medical treatment in patients who followed the standard and integrated pathways. This model examined the lifetime costs and health benefits of CEA through each pathway. Results: A total of 376 patients underwent CEA, of whom 243 were managed through the integrated stroke pathway and 133 through the standard urgent referral pathway. Median symptom to surgery time was 11 (0–66) days for the former and 15 (3–90) days for the latter ( p < .001). There was no significant difference in peri-operative stroke death rate between integrated (2.1%) and standard (1.5%) pathways (chi-square = 0.14, p = .73). CEA through the integrated pathway improved quality adjusted life expectancy by an additional 0.13 (0.64 QALYs [integrated pathway] to 0.51 QALYs [standard pathway]) and was associated with an incremental lifetime cost benefit of £2203.4. Conclusions: An integrated stroke system of care is cost-effective and associated with significant improvements in quality adjusted life years.